The Office Survival Pack: Realistic Strategies for Surviving and Winning in an Uncertain Workplace - Salam, Rudi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2025)
This study addresses the critical challenge of maintaining Workplace Resilience among Indonesian employees facing unprecedented market volatility and technological disruption, an issue underscored by global reports (WEF, 2024). Although existing theory supports Dynamic Capabilities at the organizational level (Teece, 2018) and Psychological Capital (Luthans, 2020) at the individual level, a significant gap remains in providing practical coping strategies relevant to Indonesia’s specific local work dynamics. The research adopted a qualitative-exploratory approach, utilizing in-depth interviews with 18 High Performers (HiPo) in the Indonesian MNC and startup sectors, with the aim of formulating and validating an evidence-based conceptual model: